Incidence of Underachievement in the Secondary and Higher Secondary Schools of Kerala - George , Reena; Abraham , Mercy (INDIAN EDUCATIONAL REVIEW, 2009)
The distressing phenomenon of underachievement in school subjects is a matter of great concern among researchers and educationists. The study compares the incidence of academic underachievement, among 1,730 students in the Secondary and Higher Secondary Schools of Kerala. Composite Tests of Achievement in school subjects and Raven’s Standard Progressive Matrices were the tools used. Regression analysis and Critical Ratio tests of significance were the statistical techniques employed. The study found that 15.26 per cent of students in the Secondary and Higher Secondary Schools of Kerala are underachievers in school subjects, 70.46 per cent are normal achievers and 14.28 per cent are overachievers. The proportion of underachievers is higher in the Secondary level than that in the Higher Secondary level. A higher proportion of female students are overachievers, whereas a higher proportion of male students are underachievers. The rural and urban sub-groups are homogenous with respect to the incidence of over, normal and underachievement.